2019
DOI: 10.1186/s12913-019-4317-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of working environment and benefits packages on the health professionals’ job satisfaction in selected public health facilities in eastern Ethiopia: using principal component analysis

Abstract: Background World Health Organization (WHO) predicted that there will be a shortfall of skilled healthcare by 2035 with the greatest shortfall in Africa and Southeast Asia due to satisfaction with payment and incentives. Low job satisfaction of health workers can result in increased staff turnover and absenteeism, which affects the efficiency of health services. Ethiopia has been affected by a shortage of health professionals due to a brain drain of health professionals. Our study, therefore, aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 20 publications
7
40
1
2
Order By: Relevance
“…Another is supported by a recent study, in Saudi Arabia, that showed a high prevalence of poor sleep among emergency room physicians of 83% using the PSQI [38]. In general, healthcare workers are at an increased risk of work-related stress [41]. In the current study, the mean PSS score was high, with a value of 20.3.…”
Section: Discussionsupporting
confidence: 72%
“…Another is supported by a recent study, in Saudi Arabia, that showed a high prevalence of poor sleep among emergency room physicians of 83% using the PSQI [38]. In general, healthcare workers are at an increased risk of work-related stress [41]. In the current study, the mean PSS score was high, with a value of 20.3.…”
Section: Discussionsupporting
confidence: 72%
“…The findings showed that the satisfaction level of health workers was decreased with increase in age. The result is similar to the study done in eastern Ethiopia [19]. Educationally, diploma holders were more satisfied with their work than degree holders.…”
Section: Discussionsupporting
confidence: 88%
“…The variation might happen due to differences in leadership style, the health system of the countries, infrastructure, study area, and composition of the study participants. The result is higher when compared to the result of the study conducted in eastern Ethiopia with 38.5% overall of job satisfaction [19] and, in Sabata Hawas with a 38.9% satisfaction level [15]. A previous study conducted in a similar area but only on public Hospitals had 34.9 % satisfaction [9].…”
Section: Discussionmentioning
confidence: 75%
“…The effect of working environment, coworkers support and team dynamics, team leader qualities, and nature of work assigned to workers on their overall satisfaction can also not be ignored. [373839] Ideally, it is challenging to perform international comparisons of the working environment and job satisfaction. The healthcare settings and the duties of healthcare providers with a similar designation differ between countries and differences are marked even within states.…”
Section: Discussionmentioning
confidence: 99%